An exploratory study of verbal interaction between children with different profiles of DLD and their classroom teachers in educational dialogues. (October 2019) - Bruce, Barbro; Hansson, Kristina
Children with a history of developmental language disorder (DLD) entering school are a challenge for classroom teachers. Teachers are often not very familiar with DLD, and language difficulties in school age children are often not obvious in context-supported everyday language. However, their language is still vulnerable. The teachers' way of talking with four children with DLD, two with predominantly production difficulties and stronger language comprehension and two with language comprehension difficulties were studied in two types of context, differing in their degree of structure. Variables for a quantitative analysis were number of words per minute and mean length of utterance (MLU) in words for both teachers and children, and the number of questions asked by the teacher. A qualitative analysis focused on identifying typical characteristics depending on context and the child's type of difficulties. In both contexts the teachers talked more than the children, but the difference was smaller in the less structured context, mainly because the children talked more. The two children with predominantly production difficulties seemed to take advantage of the opportunities to take initiatives offered in the less structured context. The children with comprehension difficulties function better in the more structured context, where their comprehension difficulties were less obvious. Studies with more rigorous design analysing more aspects of teacher's interactive behavior in different contexts and with children with different linguistic profiles are needed to provide teachers with information to raise their awareness of how to provide support adapted to the linguistic profiles of children with DLD.